Multiphase, Multiscale Chemomechanics at Extreme Low Temperatures: Battery Electrodes for Operation in a Wide Temperature Range (Adv. Energy Mater. 37/2021). Issue 37 (6th October 2021) - Li, Jizhou; Li, Shaofeng; Zhang, Yuxin; Yang, Yang; Russi, Silvia; Qian, Guannan; Mu, Linqin; Lee, Sang‐Jun; Yang, Zhijie; Lee, Jun‐Sik; Pianetta, Piero; Qiu, Jieshan; et al.
Abstract : Lithium‐Ion Batteries In article number 2102122, Peter Cloetens, Kejie Zhao, Feng Lin, Yijin Liu and co‐workers systematically elucidate multiphase, multiscale chemomechanical behaviors of composite lithium‐ion battery cathodes under low‐temperature conditions. Their results suggest that, in order to design batteries for use in a wide temperature range, it is critical to develop electrode components that are structurally and morphologically robust when the temperature is switched.